THE EFFECTS OF SECONDARY PREVENTION IN A PATIENT WITH CORONARY HEART DISEASE (CHD): A LITERATURE REVIEW - Gratsia Victoria Fernandez (Nursing Current: Jurnal Keperawatan, 2023)
Coronary Heart Disease (CHD) is the most common form of cardiovascular disease and one of the leading causes of death worldwide. Considering that CHD is chronic in nature, adherence to secondary prevention measures is needed to prevent the development of CHD in a worse direction, such as disability and disease recurrence. This study aimed to review the literature on secondary prevention and its effect on a patient with CHD. The search of literature used predefined keywords through several databases, namely Scopus, ProQuest, Science Direct and SAGE Journal. The inclusions are articles in full text, written in English, and published within the last five years from 2019 - 2023. The exclusions are non-experimental research literature and those that do not describe the impact of second prevention. The results show that there are fifteen articles that met the inclusion criteria. The secondprevention can be given in various ways, and media can be used according to the patient's needs. This second prevention also provides many benefits for quality of life, self-efficacy, knowledge, adherence, self-care, health behavior, lifestyle, life orientation, optimism, physical activity, levels of anxiety and depression in patients controlling cholesterol levels and blood pressure. and reduce the occurrence of complications.